2012
DOI: 10.1007/s00216-012-5980-0
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the ionic liquid cation 1-alkyl-3-methylimidazolium to p-tetranitrocalix[4]arene probed by fluorescent indicator displacement

Abstract: Acridine orange (AO) was used as a fluorescent probe molecule to study the encapsulation of an alkylimidazolium cation from a water-soluble ionic liquid (IL) within two cavitand species, p-tetranitrocalix[4]arene (1) and calix[4]resorcinarene (2), both in alkaline aqueous media. The addition of IL to the preformed [1·AO] adduct resulted in significantly increased fluorescence due to the expulsion of AO from the inclusion complex to the aqueous phase by competitive recognition of the 1-alkyl-3-methylimidazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…19 Moreover, imidazolium based ILs can form stable adducts with cation chelating/polyanion bearing molecules. 20 To further explore the potential utility of the reagent in our system, NMR titrations using model IL 3-methyl-1-imidazol-3-ium-propionate with NTA analogue N-acetyl-Na,Na-bis(carboxymethyl)-L-lysine in the absence of Ni 2+ showed that the IL interacts with the model NTA label in PBS buffer (pH 7.4) with an approximate binding constant of 22 AE 9 mM À1 (see ESI, † for details). 21 A number of cell lines, including Jurkat T-lymphocytes, breast cancer cell line MDA-MB-231 (MDA), colon cancer cell line HT29-MTX-E12 (E12), cervical cancer cells HeLa and SV40immortalized human corneal epithelium (AS) cells were incubated for 3 days 5 in the presence of a range of concentrations of 2 (0.2-200 mM).…”
mentioning
confidence: 99%
“…19 Moreover, imidazolium based ILs can form stable adducts with cation chelating/polyanion bearing molecules. 20 To further explore the potential utility of the reagent in our system, NMR titrations using model IL 3-methyl-1-imidazol-3-ium-propionate with NTA analogue N-acetyl-Na,Na-bis(carboxymethyl)-L-lysine in the absence of Ni 2+ showed that the IL interacts with the model NTA label in PBS buffer (pH 7.4) with an approximate binding constant of 22 AE 9 mM À1 (see ESI, † for details). 21 A number of cell lines, including Jurkat T-lymphocytes, breast cancer cell line MDA-MB-231 (MDA), colon cancer cell line HT29-MTX-E12 (E12), cervical cancer cells HeLa and SV40immortalized human corneal epithelium (AS) cells were incubated for 3 days 5 in the presence of a range of concentrations of 2 (0.2-200 mM).…”
mentioning
confidence: 99%